Kartogenin Induced Adipose-Derived Stem Cell Exosomes Enhance the Chondrogenic Differentiation Ability of Adipose-Derived Stem Cells. (29th August 2022) - Xie, Aiguo; Xue, Jixin; Wang, Yuting; Yang, Chao; Xu, Miao; Jiang, Yongkang
Abstract : Objective . The objective of this study is to explore the effect of kartogenin (KGN-)-pretreated adipose-derived stem cell-derived exosomes (ADSC-EXOs) on the chondrogenic differentiation ability of ADSCs. Methods . Adipose-derived stem cells (ADSCs) were treated with different doses of KGN, and exosomes (EXOs) were extracted. EXOs were then identified using an electron microscope (EM), nanoparticle tracking analyzer, nanoparticle tracking analysis software, and exosomal protein markers. EXOs were labeled with the fluorescent dye PKH67 and their uptake by cells was evaluated. A cell counting kit-8 (CCK-8) assay, flow cytometry, clonogenic assay, and a cell scratch assay were used to detect the abilities of proliferation, apoptosis, clone formation, and migration of ADSCs, respectively. Subsequently, Alcian blue staining and toluidine blue staining were used to detect the chondrogenic differentiation ability of ADSCs in each group. Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot (WB) techniques were used to detect the expression of chondrogenic differentiation-related genes. Results . In this study, ADSCs and KGN-induced ADSC-EXOs were successfully extracted and isolated. EXOs and ADSCs coculturing results showed that KGN-induced ADSC-EXOs can significantly promote proliferation, clone formation, migration, and chondrogenic differentiation of ADSCs and inhibit apoptosis. In addition, KGN-induced ADSC-EXOs can increase the expression of chondrogenic-related genes in ADSCs (Aggrecan, Collagen III, Collagen II, and SOX9), and can significantly decrease the expression of chondrolysis-related genes (MMP-3, ADAMTS4, and ADAMTS5). Conclusion . KGN-induced ADSC-EXOs can enhance the chondrogenic differentiation ability of ADSCs by promoting cell proliferation and migration while inhibiting cell apoptosis. KGN treatment can also increase the expression of chondrogenic differentiation-related genes and decrease the expression of chondrolysis-related genes. These results provide a new approach to cartilage repair and regeneration.